Histological and immunological characteristics of the junctional epithelium - Masanori Nakamura (Elsevier, 2018)
Summary: The continuity of epithelial tissue is collapsed by tooth eruption. The junctional epithelium (JE) is attached to the tooth surface by hemidesmosomes, which constitutes the front-line defense against periodontal bacterial infection. JE constitutively expresses intercellular adhesion molecule-1 (ICAM-1), and neutrophils and lymphocytes penetrate into JE via interaction between ICAM-1 and LFA-1 expressed on the surface of these migrating cells. JE also expresses cytokines and chemokines. These functions of JE are maintained even in germ-free condition. Therefore, the constitutive expression of adhesion molecules, cytokines, and chemokines might be used not only for anti-pathogenic defense but also for maintaining the physiological homeostasis of JE. In this review, we have mainly focused on the structural and functional features of JE, and discussed the function of intraepithelial lymphocytes in JE as a front-line anti-microbial defense barrier and regulator of JE hemostasis. Keywords: The junctional epithelium, Intraepithelial lymphocytes, ICAM-1, Cytokines, Chemokines, Enamel organ